MENINJAU KEMBALI KONSEP PENULARAN PEMBUNUHAN (HOMICIDE CONTAGION): MEMBEDAKAN TRANSMISI DAN PENGELOMPOKAN KEKERASAN MEMATIKAN - Zul Khaidir Kadir (Journal of Research and Publication Innovation, 2026)
The language of contagion has become increasingly attractive in homicide and mass shooting research because it appears to explain why lethal violence sometimes clusters in time, social relations, and urban space. Yet clustering does not necessarily demonstrate transmission. This article re-examines homicide contagion by asking a more restrictive question: under what conditions can a post-event increase in lethal violence reasonably be interpreted as contagion rather than pre-existing concentration, common shocks, homophily, or persistent place-based risk? A systematic literature review followed by narrative synthesis was conducted on empirical research published between January 2000 and June 2026. The review covers temporal self-excitation, media attention, offender digital traces, social-network exposure, and near-repeat homicide. The strongest temporal claims largely arise from mass-shooting datasets and remain sensitive to event definitions and model specifications. Media visibility can expand the salience of previous attacks, but aggregate news volume rarely demonstrates individual exposure. Network and spatial studies show that lethal risk is unevenly concentrated, although event dependence remains difficult to separate from shared vulnerability. The article therefore proposes selective amplification: earlier events may amplify risk only where exposure intersects with existing motives, relational conflict, network position, or persistent urban vulnerability. Homicide contagion should consequently be reserved for cases where temporal precedence, identifiable exposure, and a plausible event-dependent change in lethal risk are jointly supported.